Sustainability and machinability in hard turning under MQL conditions using nanoparticle-enriched vegetable-based fluid: an integrated assessment - Hamdi, Amine; Abderazek, Hammoudi; Yapan, Yusuf Furkan; Uysal, Alper; Merghache, Sidi Mohammed (SPRINGER LONDON LTD, 2025)
This study introduces an integrated approach for assessing both sustainability and machinability in the CNC turning of hardened AISI 1045 steel (52 HRC). The machining process employs minimum quantity lubrication (MQL) supplemented with biodegradable, vegetable oil-based nanofluids. Two distinct nanoparticle formulations are investigated: one based on multiwalled carbon nanotubes (MWCNT) and the other on hexagonal boron nitride (hBN). The study is conducted according to a Taguchi L-18 experimental design. Four critical performance indicators are assessed: surface roughness (Ra), cutting temperature (T-c), total carbon emissions (CEtotal), and overall machining cost (MCtotal). The comprehensive analysis integrated Pareto charts, multiple linear regression modeling, and experimental validation. Furthermore, multicriteria decision making using the technique for order preference by similarity to ideal solution (TOPSIS) is employed, with equal weighting (25%) assigned to each criterion. The findings reveal that the hBN-based nanofluid achieved the highest overall performance, closely followed by the MWCNT-enhanced formulation, which demonstrated notable effectiveness in thermal control and environmental impact reduction. In contrast, traditional MQL without nanoparticles proved less efficient. Moreover, the cross-analysis of Pareto diagrams revealed that the cutting condition ( CC ) is the only factor with a statistically significant effect on all measured responses.
Keywords: CNC turning; Hard steel; Sustainability; Nanofluids; Vegetable oil; MQL; Linear regression; TOPSIS; MINIMUM QUANTITY; CUTTING FLUID; DRY; OPTIMIZATION; LUBRICANT; STEEL; OIL; Automation & Control Systems; Engineering